2007
DOI: 10.2202/1542-6580.1548
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Fried Oil to Obtain Biodiesel: Zeolites Y as a Catalyst

Abstract: The transesterification reaction is the most utilized process to obtain biodiesel. Fried oil transesterification reactions with methanol have been studied using several zeolites Y and interchanged with CsCl and KOH. The reaction has been carried out both in a slurry reactor and a fixed bed catalytic reactor. The catalytic effects of zeolites have been tested within a temperature range of 60-476°C, 2.5-5% catalyst/waste oil weight ratio, and 6:1 - 100:1 methanol/oil molar ratio. Cosolvents (THF, n-hexane) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…aluminosilicates interlinked by oxygen atoms. In order to have significant catalytic effect, zeolites are synthesized with Si/Al ratios framework, adjustable acid centers and with molecular pores and channels of uniform sizes [34].…”
Section: Evolutionary Stages Of Solid Acid Catalystsmentioning
confidence: 99%
“…aluminosilicates interlinked by oxygen atoms. In order to have significant catalytic effect, zeolites are synthesized with Si/Al ratios framework, adjustable acid centers and with molecular pores and channels of uniform sizes [34].…”
Section: Evolutionary Stages Of Solid Acid Catalystsmentioning
confidence: 99%
“…Pemakaian katalis pada reaksi transesterifikasi dapat dikategorikan ke dalam beberapa kelompok, Enayati et al (2008) Penggunakan katalis padat Mg-Al Hydrocalcite dengan bahan baku canola oil menghasilkan konversi reaksi sekitar 71.9 % selama 9 jam reaksi pada temperatur 60 o C (Ilgen et al 2007). Pembuatan biodiesel dari minyak goreng bekas dengan katalis Zeolite Y menghasilkan konversi yang semakin meningkat setelah penambahan co-solvent THF dan n-Hekasana (Brito et al 2007). Konversi reaksi pada pembuatan biodiesel dari colza oil sekitar 99.89 % dengan menggunakan co-solvent THF pada suhu 60 o C dan waktu reaksi 10 menit (Caglar 2007).…”
Section: Pendahuluanunclassified
“…This limits its use as a catalyst for transesterification. Brito et al [1] studied fried oil transesterification reactions with methanol using several zeolites Y and interchanged with CaCl2 and KOH. It was observed that best yield of 98 % fatty acid methyl ester (FAME) was obtained with Y756 zeolite interchanged with KOH.…”
Section: Introductionmentioning
confidence: 99%